2005
DOI: 10.1038/nature03826
|View full text |Cite
|
Sign up to set email alerts
|

Regional insolation forcing of late Quaternary climate change in the Southern Hemisphere

Abstract: In agreement with the Milankovitch orbital forcing hypothesis it is often assumed that glacial-interglacial climate transitions occurred synchronously in the Northern and Southern hemispheres of the Earth. It is difficult to test this assumption, because of the paucity of long, continuous climate records from the Southern Hemisphere that have not been dated by tuning them to the presumed Northern Hemisphere signals. Here we present an independently dated terrestrial pollen record from a peat bog on South Islan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
165
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 142 publications
(185 citation statements)
references
References 27 publications
16
165
1
3
Order By: Relevance
“…Such correspondence between Antarctica and midlatitudes of the Southern Hemisphere has been proposed for the initiation and termination of the LGM (30), but has only recently been suggested for millennial time scales (31). Vandergoes et al (30) and Kaiser et al (31) both further suggested that the climatic link between Antarctica and the temperate midlatitudes was through variations in sea-ice extent, the Antarctic Circumpolar Current, and the westerlies, a hypothesis supported by upwelling data (36) and modelling (34). Although we cannot test this scenario directly, our proposal that high lake levels are linked to northward shifts in the pressure and storm systems around Antarctica, is consistent with this concept.…”
Section: Discussionsupporting
confidence: 73%
“…Such correspondence between Antarctica and midlatitudes of the Southern Hemisphere has been proposed for the initiation and termination of the LGM (30), but has only recently been suggested for millennial time scales (31). Vandergoes et al (30) and Kaiser et al (31) both further suggested that the climatic link between Antarctica and the temperate midlatitudes was through variations in sea-ice extent, the Antarctic Circumpolar Current, and the westerlies, a hypothesis supported by upwelling data (36) and modelling (34). Although we cannot test this scenario directly, our proposal that high lake levels are linked to northward shifts in the pressure and storm systems around Antarctica, is consistent with this concept.…”
Section: Discussionsupporting
confidence: 73%
“…However, as described above, forest persisted in the north throughout the LGM and forest pollen increased sharply in North Island sites around 18,000 years ago (Newnham et al 2003), several thousand years before there was any significant increase in atmospheric CO 2 concentration. Similarly, a mid-LGM warming and period of forest expansion evident in some NZ pollen records (Vandergoes et al 2005;Alloway et al 2007;) coincides with minimum atmospheric CO 2 concentration. If there was a CO 2 effect on flowering, it certainly was insufficient to prevent adequate forest pollen representation.…”
Section: ) Low Atmospheric Concentrations Of Co 2 At the Lgm May Havmentioning
confidence: 83%
“…However, there has been a trend towards dating lake, swamp and playa sequences using pollen preparations or bulk sediment dates on relatively inorganic materials (e.g. Gillespie et al 1991;Magee 1995;Chester and Prior 2004;Vandergoes et al 2005;Cupper 2006;). In the latter case, the carbon being dated in organic poor sediments is likely to be effectively similar to a pollen preparation concentrate.…”
Section: Introductionmentioning
confidence: 99%
“…Barrell et al (2013) suggested that full glacial conditions may have begun around 28.8 ka based on a large increase in herb pollen around this time (Vandergoes et al, 2005). Climatic amelioration occurred around 18 ka, based on pollen assemblages and speleothem records (Williams et al, 2015).…”
Section: Mis 2 (Ca 29-14 Ka) and The Glgm Period (265-19 Ka)mentioning
confidence: 99%